2020
DOI: 10.1111/mcn.12956
|View full text |Cite
|
Sign up to set email alerts
|

A measurement scale to assess responsive feeding among Cambodian young children

Abstract: The caregiver–child interaction during mealtime, which refers to responsive feeding (RF), influences child's dietary intake. In Cambodia, given the level of malnutrition, getting better knowledge of RF among young children is essential, but to do so, using an appropriate assessment tool is necessary. We aim to develop and to validate a measurement tool to assess RF in two different situations (before and after an intervention) among children 6–23 months old. This research is part of a larger trial assessing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…We decide to use the full scale score rather than the sub-scale score since the full score has more variability, owing to its higher number of items than the subscale score. However, responsive feeding is a multi-dimensional concept and was measured differently across studies [ 3 , 4 ]. Some dimensions are not included in the current scale, for example, indulgent feeding, maternal sensitivity to infant cues, and uninvolved feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We decide to use the full scale score rather than the sub-scale score since the full score has more variability, owing to its higher number of items than the subscale score. However, responsive feeding is a multi-dimensional concept and was measured differently across studies [ 3 , 4 ]. Some dimensions are not included in the current scale, for example, indulgent feeding, maternal sensitivity to infant cues, and uninvolved feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Responsive feeding is crucial to the formation of life-long healthy eating behavior [ 1 ] and is an important protective element for infant health, well-being, and development [ 2 , 3 ]. Most studies on responsive feeding thus far have been conducted in Western cultures [ 4 ] and few have examined maternal responsive feeding and associated factors in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their pioneer study, Sall et al (2020) addressed several of the shortcomings identified in the review by Heller and Mobley by developing and validating an abbreviated and pragmatic RF scale that has potential to be used in community studies and population surveys. The scale was developed using data routinely collected among 6‐ to 23‐month‐old children in rural Cambodia through the ‘Opportunistic Observation Form’ from the Process for the Promotion of Child Feeding (ProPAN) package (PAHO, WHO, & UNICEF, 2013).…”
mentioning
confidence: 99%
“…Moving forward, and given the complexity of attempting to measure all possible aspects of RF through a pragmatic scale suitable for field and populations studies, it is key that researchers ask themselves first which aspects of RF they want to focus on and why, and if they also need to incorporate abbreviated scales to measure other aspects of responsive parenting directly linked with infant and young child feeding, including sleep, soothing and physical activity (Pérez‐Escamilla et al, 2017). Lastly, because as highlighted by Sall et al (2020), different definitions of RF have been used, hence it is important to reach consensus on a single definition of this complex construct to help move this research area forward.…”
mentioning
confidence: 99%